2015
DOI: 10.1210/en.2014-1851
|View full text |Cite
|
Sign up to set email alerts
|

Positive, But Not Negative Feedback Actions of Estradiol in Adult Female Mice Require Estrogen Receptor α in Kisspeptin Neurons

Abstract: Hypothalamic kisspeptin (Kiss1) neurons express estrogen receptor α (ERα) and exert control over GnRH/LH secretion in female rodents. It has been proposed that estradiol (E2) activation of ERα in kisspeptin neurons in the arcuate nucleus (ARC) suppresses GnRH/LH secretion (negative feedback), whereas E2 activation of ERα in kisspeptin neurons in the anteroventral periventricular nucleus (AVPV) mediates the release of preovulatory GnRH/LH surges (positive feedback). To test these hypotheses, we generated mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 59 publications
10
83
0
1
Order By: Relevance
“…This rostral population of kisspeptin neuronswhich is distinct from that in the arcuate nucleus -is predominant in females; projects to the GnRH neurons; expresses ERα; has both Kiss1 and ion-channel gene expression modulated by oestradiol levels throughout the oestrous cycle; and is activated at the time of the surge 58-62 . Although not proven specifically for the RP3V kisspeptin population, the selective deletion of Εrα from all kisspeptin neurons abolishes the LH surge in mice 63 . The RP3V kisspeptin cells also receive synaptic inputs from suprachiasmatic nucleus vasopressin neurons 64,65 , although it remains unclear precisely how they modulate RP3V kisspeptin activity in a circadiandependent manner [66][67][68] .…”
Section: Rodentsmentioning
confidence: 94%
“…This rostral population of kisspeptin neuronswhich is distinct from that in the arcuate nucleus -is predominant in females; projects to the GnRH neurons; expresses ERα; has both Kiss1 and ion-channel gene expression modulated by oestradiol levels throughout the oestrous cycle; and is activated at the time of the surge 58-62 . Although not proven specifically for the RP3V kisspeptin population, the selective deletion of Εrα from all kisspeptin neurons abolishes the LH surge in mice 63 . The RP3V kisspeptin cells also receive synaptic inputs from suprachiasmatic nucleus vasopressin neurons 64,65 , although it remains unclear precisely how they modulate RP3V kisspeptin activity in a circadiandependent manner [66][67][68] .…”
Section: Rodentsmentioning
confidence: 94%
“…Classical studies have indicated that the locus of the negative feedback action of estradiol is within the MBH, and, intuitively, it might be expected that ERα expressing KNDy neurons in the arcuate nucleus are the neuronal phenotype targeted. Intriguingly, however, a recent study by Levine and his colleagues employing transgenic mice null for ERα in kisspeptin neurons (not restricted to KNDy neurons) has failed to support this notion (Dubois, et al 2015). On the other hand, Herbison’s group using genetically engineered adult female mice and adeno-associated virus injection into the arcuate nucleus to delete approximately 75% of ERα positive cells in this nucleus abolished chronic negative feedback action of estradiol on LH secretion (Yeo and Herbison 2014) 4 .…”
Section: Neuroendocrine Control Of Ovarian Cyclesmentioning
confidence: 99%
“…Evidence suggests that oestrogen acts via the oestrogen receptor ERα on kisspeptin neurons (Dubois et al 2015) to exert negative feedback on GnRH release (Smith et al 2005a,b). Expression of Dyn and NKB is also influenced by oestrogen, with expression of Dyn, NKB, the KOR gene and the NKB receptor gene all inhibited by oestrogen in animal models created (Navarro et al 2009).…”
Section: Kisspeptin and Its Physiological Role As A Gnrh Modulatormentioning
confidence: 99%